O apelo ético do rosto em Emmanuel Levinas - Nascimento, Carlos Eduardo Santos (2022)
This study was done to investigate the question of alterity through the concept of Face into the original Totality and Infinity written by Emmanuel Levinas. The Face is the reading key to understand Levinas' ethical proposal, since in that Face, the Other is presented in its most absolute otherness. Emphasizing the human Face´s ethical appeal, our research explores how, from a scathing critique to the totality which permeates the entire philosophy history and Western culture, Levinas understands alterity in its infinite condition. With approximations and distances from the phenomenological method in his analysis of the Face, especially in sections 1st and 3rd in the work Totality and Infinity, this dissertation tries to understand and describe how subjectivity becomes responsibility to the Other, as a response to the ethical appeal of the Face, this founding principle of sociality, true human sense in Levinas.